The Role Of Village Forest Community Institutions In Empowering The Community In The Songgon Pine Forest, Banyuwangi - Dina Suryawati; Panca Oktawirani; Ihsan Aji Santoso (Universitas Muhammadiyah Jember Press, 2025)
Indonesia has significant potential for social forestry, implemented through schemes such as the Forest Village Community Institution (Lembaga Masyarakat Desa Hutan - LMDH). This study analyzes the role of the LMDH Rimba Ayu in empowering the community in the Songgon Pine Forest area, Sumberbulu Village, Banyuwangi. The research focuses on describing the meaning and implementation of the LMDH's roles, interpreting the manifestation of publicness values in its institutional practices, and identifying the supporting and inhibiting factors for its effectiveness as a bridging institution between the state (Perhutani), the market, and the local community. This research uses a qualitative approach with a descriptive case study design. Data were collected through participant observation, in-depth interviews with LMDH administrators, community members, and Perhutani representatives, as well as documentation studies. Data analysis followed the interactive model of Miles and Huberman, supplemented by triangulation to ensure data validity. The results indicate that LMDH Rimba Ayu plays a strategic role as a facilitator, motivator, and coordinator in community empowerment. This role has transformed the local economy by increasing average community income by up to 40% through ecotourism, while simultaneously suppressing illegal logging cases. The values of publicness are manifested in practices such as community participation in deliberations, transparent financial reporting, and a public interest orientation through the allocation of village social funds. The LMDH also functions effectively as a bridging institution, mediating and connecting the interests of multiple stakeholders (community, Perhutani, village government). Key supporting factors include policy legitimacy from Perhutani, strong local leadership, and social solidarity. Conversely, inhibiting factors include dependency on top-down policies, uneven human resource capacity, and infrastructure limitations. Keywords: Forest Village Community Institution (LMDH), Community Empowerment, Publicness, Bridging Institution, Ecotourism, Social Forestry.